Thromboelastography in Patients with Acute Ischemic Stroke - Elliott, Andrea (2012)
BACKGROUND: Thromboelastography (TEG) measures the dynamics of coagulation. There are limited data about TEG in acute ischemic stroke other than a single study from 1974 suggesting that acute ischemic stroke patients are hypercoagulable. There have been no studies of TEG in the thrombolytic era despite its potential usefulness as a measure of clot lysis. This study was designed to provide initial TEG data in stroke patients before and after tissue plasminogen activator (tPA) therapy, and to provide the necessary preliminary data for further study of TEG’s ability to identify clot subtype and predict response to tPA therapy. METHODS: All acute ischemic stroke patients presenting between 11/2009 and 2/2011 eligible for tPA therapy were screened and 56 enrolled. Blood was drawn before (52 patients) and 10 minutes after tPA bolus (30 patients). Demographics, vitals, labs, 24hr National Institutes of Health Stroke Scale (NIHSS) and computed tomography (CT) scan results were collected. Patients were compared to normal controls. RESULTS: Acute ischemic stroke patients had shorter R (4.8±1.5 vs 6.0 ±1.7 min, p =0.0004), greater a-Angle (65.0±7.6 vs 61.5 ± 5.9°, p =0.01), and shorter K (1.7 ±0.7 vs 2.1 ±0.7 min, p =0.002) indicating faster clotting. Additionally, a subset formed clots with stronger platelet-fibrin matrices. Treatment with tPA resulted in reduction in all indices of clot strength (LY30=0(0–0.4) vs 94.4 (15.2–95.3) p<0.0001), however there was considerable variability in response. CONCLUSIONS: TEG demonstrates that many acute ischemic stroke patients are hypercoaguable. TEG values reflect variable clot subtype and response to tPA. Further study based on these data will determine if TEG is useful for measuring the dynamic aspects of clot formation and monitoring lytic therapy.